The Influence of Air-Fuel Equivalence Ratio on the Perfor-mance and Emission Characteristics of a Crank-rocker Engine - Mohammed, Salah E.; Baharom, M. B.; A. Aziz, A. Rashid (International Journal of Engineering and Technology, 2018)
This paper investigates the effect of air-fuel equivalence ratio on the crank-rocker engine performance and emission. The engine is a four-stroke single curved-cylinder spark ignition gasoline engine. The experiment was conducted at different equivalence ratios of 0.7, 0.96, 1.15, and 1.21 with each one operating at 50% throttle. The entire tests were carried out at an engine speed of 2000 rpm and 6.5Â° CA BTDC ignition timing. The performance data such as brake torque, brake power, brake specific fuel consumption, and brake thermal efficiency were calculated. The engine exhaust gas emission such as CO, CO2, HC, and NOx have also been measured. The results showed that the maximum values for the brake torque and power occurred when air-fuel equivalence ratio was equal to 0.91. While the minimum brake specific fuel consumption occurred when the equivalence ratio was equal to 1.15; which is the point of the maximum brake thermal efficiency. From the experimental results, it was found that the concentration of CO and HC emissions decreased while CO2 and NOx emissions increased with the increase in air-fuel equivalence ratio. To conclude, the crank-rocker engine may become an alternative to the conventional engine in the future but further research work will be required.Â